Hybridizing kenaf and glass fibres as reinforcement in ABS composites: current trends, properties and potential application in aircraft radome - Muhammad Fauzi Muhammad Fitri,; Muhammad Rizal Muhammad Asyraf,; Shukur Abu Hassan, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The advancement of thermoplastic composites reinforced with hybrid kenaf/glass fibres has rapidly progressed, positioning them as viable structural materials for diverse industries. The incorporation of hybrid kenaf/glass fibres in these composites aims to introduce new dimensions of sustainability. This is driven by the superior strength, stiffness, and lightweight properties exhibited by the hybrid composites, making them well-suited for high-end structural applications. Furthermore, the hybrid kenaf/glass fibres composites offer economic advantages and various benefits, including recyclability, cost-effectiveness, biodegradability, and wide availability. Currently, these emerging composites are gaining attention in industries such as automotive, defence, aerospace, marine, construction, and naval sectors. Despite their increasing popularity, there is a notable gap in the literature, as comprehensive focus on the recent progress of hybrid kenaf/glass fibres reinforced ABS composites for structural applications is lacking. Therefore, this review paper critically discusses recent findings related to the physical, mechanical, and energy absorption properties, as well as processing techniques, of kenaf fibres and their hybrids with ABS matrix materials for aircraft radome. The article also aims to underscore the significance of hybrid kenaf/glass reinforced ABS composites in enhancing mechanical performance for applications requiring radome structures. This review also found out that the composites with quasi-isotropic sequence which combine with ±45-degree fibre orientation provide superior mechanical properties. The ±45-degree stacking is expected to enhance the mechanical properties because it offers balanced in-plane stiffness and strength as well as, improved shear properties. This orientation distributes the stresses more evenly throughout the composite material, leading to improved damage tolerance and impact resistance, which are critical for the structural integrity and durability of aircraft radomes.